Enzyme/pH-triggered anticancer drug delivery of chondroitin sulfate modified doxorubicin nanocrystal. Issue 1 (1st January 2020) - Liang, Yan; Fu, Xiaoheng; Du, Chen; Xia, Haoran; Lai, Yusi; Sun, Yong
Abstract: In this paper, we developed a novel strategy of preparing doxorubicin (DOX) nanocrystal (NC) exerting spherical particles with a diameter of 102 nm, which experienced following coating of chondroitin sulphate derivative (CSOA) shell via electrostatic and hydrophobic interactions. Such multifunctional outerwear resulted in drug nanocapsules with high drug loading content up to 70% and high colloidal stability under physiological conditions. It exhibited accelerated drug release behaviour when dispersing in hyaluronidase (HAase) containing medium or incubated with cancer cells. CSOA/NCs were effectively taken up by cancer cells via CD44 receptor-mediated endocytosis, but were rarely internalised into normal fibroblasts. With the comparison of typical drug-loaded micelles system (DOX/PEG-PCL), CSOA/NCs showed greater inhibition to cancer cells due to the targeted and sensitive drug delivery.